PENGARUH PROFITABILITAS DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK PENGHASILAN WAJIB PAJAK BADAN - Prasista, Putu Meita; Setiawan, Ery (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of profitability and Corporate Social Responsibility disclosure to Income Tax aggressiveness of the taxpayer. Income Tax aggressiveness measurement in this study using Effective Tax Rates. Measurement of profitability in this study using Return On Asset, the Corporate Social Responsibility disclosure is measured by using Corporate Social Responsibility Index. Number of observations of 51 samples obtained through non-probability sampling method, ie purposive sampling. The analysis technique used is multiple linear regression, whereas the method of data collection is done by non-participant observation and documentation. The results showed that the profitability and Corporate Social Responsibility disclosure effect significantly on the Income Tax aggressiveness of the taxpayer.
Keywords: tax aggressiveness; profitability; the disclosure of Corporate Social Responsibility